2017
DOI: 10.1002/acn3.512
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive clinico‐radiological paradox in early stages of multiple sclerosis

Abstract: ObjectiveTo investigate whether the strength of the association between magnetic resonance imaging (MRI) metrics and cognitive outcomes differs between various multiple sclerosis subpopulations.MethodsA total of 1052 patients were included in this large cross‐sectional study. Brain MRI (T1 and T2 lesion volume and brain parenchymal fraction) and neuropsychological assessment (Brief International Cognitive Assessment for Multiple Sclerosis and Paced Auditory Serial Addition Test) were performed.ResultsWeak corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
2
24
2
Order By: Relevance
“…In contrast, CI of all included patients was confirmed through detailed NPA by an experienced neuropsychologist. Although in accordance with the Germany guideline on neuropsychological evaluation [25], our criterion, again introduced in retrospect for quality assurance, of a documented performance score below − 1z in at least two domains is liberal compared to other studies [4][5][6][7][8][9]11]. However, in these studies, cohorts with higher EDSS and longer disease durations were investigated (more than 10 years [4, 6-9, 11] and more than 7 years [5], respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, CI of all included patients was confirmed through detailed NPA by an experienced neuropsychologist. Although in accordance with the Germany guideline on neuropsychological evaluation [25], our criterion, again introduced in retrospect for quality assurance, of a documented performance score below − 1z in at least two domains is liberal compared to other studies [4][5][6][7][8][9]11]. However, in these studies, cohorts with higher EDSS and longer disease durations were investigated (more than 10 years [4, 6-9, 11] and more than 7 years [5], respectively).…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest magnetic resonance imaging (MRI) studies on CI in MS [2] reported a strong relationship between CI and white matter lesions (WML) compatible with the classic idea of a disconnection syndrome [3]. In later MRI studies, relations of CI to deep and cortical grey matter (GM) atrophy were reported [4][5][6][7][8][9][10][11]. When we, to the best of our knowledge, reviewed the ten structural brain MRI studies on CI in MS, with the highest numbers of CI patients included [4][5][6][7][8][9][10][11][12][13], we observed inconsistent results with regard to the contribution of WML load and GM atrophy to CI in MS.…”
Section: Introductionmentioning
confidence: 99%
“…long disease duration, old age, high physical disability, high MRI lesion load and high brain atrophy). 22 This association is also the case with brain atrophy. In contrast, a recent longitudinal study showed that T2 lesion volume and its change at earlier time points remained predictive of disability, even after 20 years, in patients with clinically isolated syndrome.…”
Section: Conventional Brain Imagingmentioning
confidence: 76%
“…[18][19][20] In addition, the magnitude of the association was highly variable among studies. 22 This association is also the case with brain atrophy. A recent cross-sectional study of a large cohort of well-defined patients with relapsing-remitting MS (RRMS) showed that the strength of the association between brain MRI measures and CI was relatively low in patients with low disease burden (i.e.…”
Section: Introductionmentioning
confidence: 76%
“…short disease duration, young age, low physical disability, low MRI lesion load and low brain atrophy), whereas it was high in those with a high disease burden (i.e. long disease duration, old age, high physical disability, high MRI lesion load and high brain atrophy) . He also mentioned the recent reports utilizing non‐conventional brain imaging, such as magnetizing transfer imaging and diffusion tensor imaging.…”
mentioning
confidence: 99%